AN ANALYSIS OF STUDENTS’ SKILL IN IMPLEMENTING PERSONAL PRONOUNS - Urip Widodo (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2020)
EFL learnears tend to have some difficulties in learning structure. They assume that learning structure is something terrible. This research aims at identifying students’ learning ability in using PERSONAL PRONOUNS and elaborating the problems faced. A case study is used to know how the students IMPLEMENT PERSONAL PRONOUNS in certain sentence. Test is used as the main instrument to know the students’ ability in using simple present tense. Meanwhile, observation and documentaion are techniques used to know the difficulties faced. There are 30 students to be researched. Based on the data analysis is known that that all of the students are considered succeed. Other classification indicates that seven students got A (23,3%), ten students got B (33,3%), and thirteen students got C (43,3%). The problem faced by the students are difficulty in memorizing the vocabularies and difficulty in understanding the meaning of personal pronouns and less motivation. Keywords: personal pronouns, analysis, learning difficulties, case study.